Multilingual Education :Teacher’s Perspectives on Oppurtunities and Challenges at Basic Level Students - Himan Rai (MultiTech Publisher, 2023)
This study entitled ‘Multilingual Education: opportunities and challenges’ which is qualitative in nature. The aim of this study is to explore teacher’s perspective on opportunities and challenges of multilingual education at primary level students. in Nepal. To conduct my study, I have used primary as well as secondary sources of data collection. For its primary sources of data, I have conducted semi-structured interview with a teacher of a public school at basic level to find out their perception towards multilingual education. For secondary sources of data, I have reviewed different policies, research papers and constitution of Nepal etc. The findings of this study included; the students have better understanding over subject matter and they have good proficiency in language. It was also found that there were some challenges that all the teachers are not multilingual, and there is problem in classroom management. At last, we understood, that multilingual education system is good for quality education but the occurred challenges should be minimized by all the stakeholders.